An adolescent female African elephant (Loxodonta africana) gave birth to an abnormal calf - Yujing Duan; Zhencun Wang; Jiangtao Li; Meng Zhang; Zhenchao Bi (Veterinary Medicine and Science, 2024)
Abstract Maternal nutrition and the uterine environment can influence placental development in mammals, leading to the birth of abnormal infants who often experience difficulties in independent standing. This article documents an adolescent female African elephant (Loxodonta africana) giving birth to an African elephant calf with a shoulder height below the mean, and its inability to stand for the first 10 h after birth, a time span that significantly exceeds the average duration for independent standing. Through the implementation of assisted feeding and assisted standing measures, the calf eventually achieved independent standing and nursing from its mother after 27 h and subsequent catch‐up growth at 5 months of age. This study presents the first case report on the growth parameters during pregnancy of an adolescent African elephant, the birth and care (feeding, assisted standing) of a small African elephant calf with the inability to stand alone and nurse independently for several hours, highlighting pregnancy may influence the growth of cows during their ongoing growth and development phase, the calf's survival and subsequent catch‐up growth at 5 months of age. These findings offer valuable insights into the care of abnormal African elephant calves.